the effect of the guided inquiry learning model on science learning outcomes - harmedi yulian saputra; Monica Prima Sari (Department of Science Education, 2022)
This study aims to figure out the effect of Guided Inquiry Learning model on learning outcomes of students in science learning. This research is motivated by a lot of research on the effect of Guided Inquiry Learning on student learning outcomes. This research is an ex-post facto research with descriptive data analysis. The population in this study were all articles originating from indexed journals related to the effect of Guided Inquiri Learning on student learning outcomes. The sample used was 10 Scopus indexed articles and SINTA accredited. Based on the results of the analysis of the articles conducted, it was found that the Guided Inquiry Learning model had a positive influence on learning outcomes seen from the cognitive, affective, and psychomotor domains in the form of increasing student learning outcomes and activities in science learning.